Caminhos de alunos com deficiências à educação de jovens e adultos: conhecendo e compreendendo trajetórias escolares - Tinós, Lúcia Maria Santos (2010)
Studies indicate that the Youngster and Adult Education program has been increasingly used as an educational resource by handicapped people. Although the last decades has shown progress in the legislation aiming to assure the right to a quality education for the students with special needs, including the handicapped ones, based on the principle of an Inclusive Education for all, the question is how the educational services special or regular - are being assured and taken into account for these individuals stands. Based on this question, the objective of this study was to understand the educational trajectories of the handicapped students that are participating in the Youngster and Adult Education program, worth the aim of, better definig the different educational services experienced by these students, including the Youngster and Adult Education program itself. To achier does, it were carried out interviews with two handicapped women enrolled in the Youngster and Adult Education program, and their mothers. For the data analysis, phenomenological understandings were selected, having as a principle the units of meanings, in order to unveil the understandings and meanings of each participants, perceptions then world of interpretations of the experienced contexts. The description of educational trajectories enabled the understanding of some aspects of the educational services (the Special School, the Special Education Classroom, the Regular Education Classroom (Inclusion) and the Youngster and Adult Education program Classes). The understanding analysis allowed to point out convergences and divergences of the analyzed processes: pedagogical attendance; academic degree; exclusion situations; welcoming; referral; certification; right or assurance; inclusion; education and work world, all descend lousy the legislations in effect. Thus, it was observed in these trajectories that the progresses in the legislation regarding the assurance of the right to a quality education, and, in this case, towards the handicapped students, still need to be put into effect with seriousness and real conditions. That these educational services, including the youngster and adult Education program, start to be thought and guaranteed for public politics that recognize the right and the necessities of the handicapped student.